Factors influencing user satisfaction on the e-filing tax return in Malaysia: a conceptual framework - Nurjeehan Ayub; Fithriah Ab Rahim; Sharinah Puasa; Nur Farahah Mohd Pauzi (Labuan Faculty of International Finance, Universiti Malaysia Sabah, 2023)
The Inland Revenue Board (IRB) started the e-government programme, which includes Electronic Tax Filing (ETF), at the beginning of 2006 to solve issues with the manual filing method. The government of Malaysia strives to ensure a transparent and accurate execution of the law, which encourages intentional compliance and electronic filing to increase competitiveness, save time and cut costs. Still, putting in place an information system is only deemed successful if users continue to utilise it after initial adoption. In earlier Malaysian studies on user satisfaction, using an e-filing system was found to have a strong association with a person's perception of risk. Nevertheless, evidence pertinent to the relationship between the untraceable claim and the receipt and user satisfaction is marginal and inclusive. Therefore, this study proposes a conceptual framework to understand the effect of untraceable claim and receipt, service quality and responsiveness on e-filling user satisfaction. The main motivation of this study is to increase user satisfaction with the e-filling system. From the synthesis of the literature review, the study identified untraceable claims and receipts, service quality and responsiveness that influence user satisfaction with e-filling. The study contributes to our understanding of the factors that influence user satisfaction with the system. This work is based on a conceptual framework that has not yet been empirically tested. Generally, this study provides a fresh fact for the practitioner concerning e-filling user satisfaction.